A Criminal Power : James Baldwin and the Law - Miller, D. Quentin (Daniel Quentin), 1967- (Book collections on Project MUSE., 2012)
James Baldwin, one of the major African American writers of the twentieth century, has been the subject of a substantial body of literary criticism. As a prolific and experimental author with a marginalized perspective--a black man during segregation and the Civil Rights era, a gay man at a time when homophobia was commonly accepted--Baldwin has fascinated readers for over half a century. Yet Baldwin's critics have tended to separate his weighty, complex body of work and to examine it piecemeal. A Criminal Power: James Baldwin and the Law is the first thematic study to analyze the complete scope of his work. It accomplishes this through an expansive definition and thorough analysis of the social force that oppressed Baldwin throughout his life: namely, the law. Baldwin, who died in 1987, attempted suicide in 1949 at the age of 25 after spending eight days in a French prison following an absurd arrest for "receiving stolen goods"--A sheet that his acquaintance had taken from a hotel. This seemingly trivial incident made Baldwin painfully aware of what he would later call the law's "criminal power." Previously, most book-length studies addressing Baldwin's entire career have been biographies and artistic "portraits." D. Quentin Miller corrects this oversight in a comprehensive volume that speaks to Baldwin's unified body of work. Miller asserts that the Baldwin corpus is a testament to how the abuse of power within the American legal, judicial, and penal systems manifested itself in the twentieth century"--Adapted from publisher's description